Family characteristics, phylogenetic reconstruction, and potential applications of the plant BAHD acyltransferase family - Xu, Donghuan; Wang, Zhong; Zhuang, Weibing; Wang, Tao; Xie, Yinfeng (Frontiers in Plant Science, 2023)
Acylation, a common chemical modification in plants, is involved in plant growth and development, as well as in the response to external environmental stresses.The BAHD acyltransferase family is a class of unique proteins in plants that can acylate a variety of primary and specialized secondary metabolites. The typically acylated products have greatly improved stability, lipid solubility, and bioavailability and thus show significant differences in their physicochemical properties and pharmacological activities. Here, we review the protein structure, catalytic mechanism, and phylogenetic reconstruction of plant BAHD acyltransferases to describe their family characteristics, acylation reactions, and the processes of potential functional differentiation. Moreover, the potential applications of the BAHD family in human activities are discussed from the perspectives of improving the quality of economic plants, enhancing the efficacy of medicinal plants, improving plant biomass for use in biofuel, and promoting the stress resistance of land plants. This review provides a reference for the research and production of plant BAHD acyltransferases.